2009
DOI: 10.1084/jem.20081984
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of HLA-B*5703 HIV-1 escape mutations in HLA-B*5703–positive individuals and their transmission recipients

Abstract: HLA-B*57 is the class I allele most consistently associated with control of human immunodeficiency virus (HIV) replication, which may be linked to the specific HIV peptides that this allele presents to cytotoxic T lymphocytes (CTLs), and the resulting efficacy of these cellular immune responses. In two HIV C clade–infected populations in South Africa and Zambia, we sought to elucidate the role of HLA-B*5703 in HIV disease outcome. HLA-B*5703–restricted CTL responses select for escape mutations in three Gag p24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
225
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 163 publications
(245 citation statements)
references
References 42 publications
18
225
1
Order By: Relevance
“…Similarly, Yu et al showed that differences in KF11 evolution between clades B and C were largely the result of differences in immunological features of HLA-B*5701-and -B*5703-restricted responses, with the latter allele being more frequent in clade C-infected populations (47). The temporality of selection can also differ between clades; while TW10 and IW9 selection is similar between clade B and C, the order in which they are selected is opposite (12). Our data show that virological factors (i.e., sequence differences) can also lead to clade-specific es- cape.…”
Section: ϫ7mentioning
confidence: 99%
“…Similarly, Yu et al showed that differences in KF11 evolution between clades B and C were largely the result of differences in immunological features of HLA-B*5701-and -B*5703-restricted responses, with the latter allele being more frequent in clade C-infected populations (47). The temporality of selection can also differ between clades; while TW10 and IW9 selection is similar between clade B and C, the order in which they are selected is opposite (12). Our data show that virological factors (i.e., sequence differences) can also lead to clade-specific es- cape.…”
Section: ϫ7mentioning
confidence: 99%
“…Molecular cloning of HIV-1 genomes is labor intensive and thus limits the number of IMCs that can reasonably be characterized. Moreover, predicting which viral genomes are functional in chronically infected individuals is challenging, because immune escape mutations frequently incur fitness costs (38)(39)(40)(41)(42)(43)(44)(45). Virus isolation represents an alternative to cloning, but bulk cultures cannot account for the biological variation of individual quasispecies members.…”
Section: Generation Of Limiting Dilution Hiv-1 Isolates From Sexual Tmentioning
confidence: 99%
“…The change from Ala to Pro at residue 146 of Gag (A146P) is a well-analyzed case. A146P is an escape selected by not only HLA-B*57-restricted, ISW9-specific CTLs (22) but also by HLA-B*15:10-restricted and HLA-B*48:01-restricted CTLs (15,23,24), although the latter CTLs selected it by different mechanisms. The replacement of Thr with Asn at residue 242 (T242N) of Gag is another case.…”
mentioning
confidence: 99%